A study on the influence of ligand variation on formamidinate complexes of yttrium: new precursors for atomic layer deposition of yttrium oxide. Issue 37 (24th August 2021) - Beer, Sebastian M. J.; Boysen, Nils; Muriqi, Arbresha; Zanders, David; Berning, Thomas; Rogalla, Detlef; Bock, Claudia; Nolan, Michael; Devi, Anjana
Abstract : Side chain variation of yttrium formamidinates yielding thermally stable precursor for water assisted ALD of dielectric Y2O3 thin films. Abstract : The synthesis and characterization of a series of closely related Y(iii ) compounds comprising the formamidinate ligands (RNCHNR) (R = alkyl) is reported, with the scope of using them as prospective precursors for atomic layer deposition (ALD) of yttrium oxide (Y2 O3 ) thin films. The influence of the side chain variation on the thermal properties of the resulting complexes is studied and benchmarked by thermal analysis and vapor pressure measurements. Density functional theory (DFT) studies give theoretical insights into the reactivity of the compounds towards water, which was targeted as a co-reactant for the deposition of Y2 O3 via thermal ALD in the next step. Among the four complexes analyzed, tris( N, N ′-di- tert -butyl-formamidinato)yttrium(iii ) [Y( t Bu2 -famd)3 ] 1 was found to possess enhanced thermal stability and was selected for Y2 O3 ALD process development. A broad ALD window ranging from 200 °C to 325 °C was obtained, yielding films of high compositional quality. Furthermore, with a film density of (4.95 ± 0.05) g cm −1 close to the bulk value, polycrystalline fcc Y2 O3 layers with a smooth topography resulted in promising dielectric properties when implemented in metal insulator semiconductor (MIS) capacitor structures.